Øv – A Problem for Categorization - Miltersen, Ehm Hjorth (Scandinavian Studies in Language, 2019)
The Danish word øv is traditionally categorized as an interjection. However, in a set of data primarily from chat conversations, several instances of øv do not match any traditional definition of interjections: It is syntactically integrated and thus does not constitute a full utterance on its own, and its semantic-pragmatic use is more nuanced than “expressing an aspect of the speaker’s mental state”. Th e main part of the article is a functionally-based analysis of these instances of øv, the insights from which are used to question the general practice of lexical categorization. I argue that a pragmatically based model of categorization is better able to account for the full range of uses for a word form.